The Malleability Narrative in Entertainment and Social Media: Explaining Pathways to Happiness in Media Content - Vandenbosch, Laura and Eggermont, Steven (Communication Theory, 2021)
Abstract Media effects research has documented the prevalence of different ideals in media content, and their effects on media users. We developed a framework for the representation of such ideals, and that may increase our understanding of the effects media have on users' well-being. Drawing on cultural sociology, communication theory, and psychological literature, we introduce the malleability narrative of mediated ideals, described as “a collection of media representations of a variety of ideals that tend to be portrayed as within reach for anyone who is committed to pursuing his/her own self-interest.” The aim of the framework is to foster content analytical research on the occurrence of the malleability narrative in popular media and to stimulate audience research on interactions between media users and the malleability narrative in media, while taking account of different explanatory routes and the heterogeneity of the audience.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA5My9jdC9xdHowNDE